“I wish someone would explain why I am in care”: The impact of children and young people’s lack of understanding of why they are in out-of-home care on their well-being and felt security - Selwyn, J; Staines, J (Wiley, 2020)
Having a good understanding of one's origins and history is known to be significant in identity development. Drawing on a large‐scale online survey of looked after children's subjective well‐being, this paper demonstrates that a significant number of children and young people (age 4–18 years) did not fully understand the reasons for their entry to care. The paper explores the effect of this lack of knowledge on children's well‐being and on their feelings of being settled in their current placement. The study reiterates the need for professionals to be honest and open with children in out‐of‐home care and the need to specifically address, perhaps repeatedly, why a child is not living with their birth family.